Pendidikan Remaja untuk Menyongsong Masa Depan Bangsa - Syamsudin (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2020)
Teenagers are the people to come. It can be estimated that the present image of adolescents is a reflection of the future community. But the reality has shown that the changing times which are accompanied by advances in science and technology always result in social changes. This cannot be underestimated because youth is a miniature of the nation's future. From the morals, character and work that will bring the country more advanced and compete in the rigors of the current era of globalization.